Self-Management in Elderly People With Diabetes Mellitus and Multiple Comorbidities - Tobi Pitora; Dzikra Fitria Amita; Dinda Nur Fajri HB; Helza Risdianti; Suprayogi Suprayogi; Irwan Agustian; Reza Indra Wiguna; Muhammad Chairul Aris; Riyda Ma’arifatul Khoirot; Annisa Pratiwi Gunawan (Proceeding of the International Conference on Health Sciences and Nursing, 2026)
Diabetes Mellitus is a chronic metabolic disorder with a rapidly increasing prevalence worldwide, particularly among the elderly population. Older adults with diabetes frequently experience multiple comorbidities that may complicate disease management, increase treatment burden, and reduce quality of life. Consequently, effective self-management is essential to maintain glycemic control and prevent complications. This study aimed to identify and analyze self-management among elderly individuals with diabetes mellitus and multiple comorbidities through a literature review. Methods: This study employed a literature review design using the PRISMA framework, including identification, screening, eligibility assessment, and synthesis of selected studies. A systematic search was conducted through PubMed, Scopus, and EBSCO. Articles published within the last five years were included. A total of 5,934 articles were identified from the three databases. Following the removal of duplicates, abstract screening, and evaluation based on inclusion and exclusion criteria, seven studies were selected for analysis. The review indicated that self-management among older adults with diabetes mellitus remains suboptimal. Major challenges included dietary regulation, physical activity, blood glucose monitoring, and medication adherence. Physical and psychological conditions were also found to significantly influence self-management abilities. Self-management among elderly individuals with diabetes and multiple comorbidities requires further improvement through continuous health education, enhancement of self-efficacy, and strong social and family support to reduce complications and improve quality of life.